Representation of Women in the Digital Age: A Journey Through Selected New Generation Malayalam Movies - Sukumar, Pavithra; Meenu B (International Journal of Psychosocial Rehabilitation, 2020)
Film is an indispensable piece of our everyday lives which impacts the manner in which we see ourselves and the world. Film is a medium which builds the images of men and women. However, the portrayal may fluctuate as per the distinctions in the attributes of the character they are presenting. Through this paper I intend to investigate how the male predominant Malayalam film industry depicts strong female characters. Malayalam film industry has been undergoing a change in its representation of women characters. Instead of previously stereotypical representations, now there is an attempt to present them as more solid characters. However, we could likewise discover certain loopholes in the screen-play where she is constantly under the dominance of her better half or sweetheart in the household circle. Typically, film is considered as one of the realistic and practical works of art which reflects and speaks to our society which is truly a male centric one. Simone De Beauvoir’s statement, “ ‘One is not born, but rather becomes, a woman’ is particularly pertinent with regards to new media as it assumes a significant job in strengthening certain cultural standards and practices”(Budgeon).Therefore, this investigation is a thorough analysis of the depiction of women in new generation Malayalam movies which revolve around marriage and love. The researcher has included two financially fruitful Malayalam movies of a decade ago; How Old Are You and 22 Female Kottayam, focusing on the female heroes Nirupama Rajeevan and Tessa K Abraham respectively. In this manner, this paper attempts to investigate how gender issues are spoken to in these movies as film is a significant zone of study since it shows what is socially acceptable.